2020
DOI: 10.1002/slct.202003287
|View full text |Cite
|
Sign up to set email alerts
|

P‐doped TiO2 Nanofibers Decorated with Ag Nanoparticles for Enhanced Photocatalytic Activity under Simulated Solar Light

Abstract: We report the synthesis of titania nanofibers (TNF) of ∼ 195 nm mean diameter doped with phosphorus through one-pot electrospinning followed by decoration of Ag nanoparticles (NPs). The Ag NPs of ∼ 8 nm size on 2 % P-doped TNFs (Ag-PTNFs) showed excellent photocatalytic activity for the reduction of Cr(VI), under simulated solar light, with ∼ 100 % conversion to Cr(III) in 90 min at pH 3 with a pseudo-first order rate constant of 0.085 min À 1 that is 96.5 % higher than TNFs. The Ag-PTNFs also exhibited excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…As shown in Figure 2c, the P 2 p spectrum of Ru/P‐TiO 2 exhibited two peaks (at 133.2 and 134.3 eV), indicating the existence of P in the pentavalent state only; [27] no signals were detected for P−M (M=Ru or Ti) bonds in the range of 129–130 eV [28] . As previously reported, [29] doped P is more likely to be located at the surface or near the surface region of octahedral sites than those of tetrahedron sites; thus, the Ti 4+ sites were partially substituted with P 5+ , forming Ti−O−P bonds [30] . The slight negative shift of the BE of the P−O bonds in P‐TiO 2 (≈0.1 eV) compared to that of Ru/P‐TiO 2 indicated the formation of Ti−O(Ru)−P bonds in Ru/P‐TiO 2 .…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…As shown in Figure 2c, the P 2 p spectrum of Ru/P‐TiO 2 exhibited two peaks (at 133.2 and 134.3 eV), indicating the existence of P in the pentavalent state only; [27] no signals were detected for P−M (M=Ru or Ti) bonds in the range of 129–130 eV [28] . As previously reported, [29] doped P is more likely to be located at the surface or near the surface region of octahedral sites than those of tetrahedron sites; thus, the Ti 4+ sites were partially substituted with P 5+ , forming Ti−O−P bonds [30] . The slight negative shift of the BE of the P−O bonds in P‐TiO 2 (≈0.1 eV) compared to that of Ru/P‐TiO 2 indicated the formation of Ti−O(Ru)−P bonds in Ru/P‐TiO 2 .…”
Section: Resultsmentioning
confidence: 71%
“…[28] As previously reported, [29] doped P is more likely to be located at the surface or near the surface region of octahedral sites than those of tetrahedron sites; thus, the Ti 4 + sites were partially substituted with P 5 + , forming TiÀ OÀ P bonds. [30] The slight negative shift of the BE of the PÀ O bonds in P-TiO 2 ( � 0.1 eV) compared to that of Ru/P-TiO 2 indicated the formation of TiÀ O(Ru)À P bonds in Ru/ P-TiO 2 . The increase in oxygen vacancies of Ru/P-TiO 2 was also confirmed by the O 1s XPS (Figure S12) and electron paramagnetic resonance (EPR) (Figure S13) spectra of Ru/ P-TiO 2 .…”
Section: Resultsmentioning
confidence: 96%
“…The FNRCS value of a material system was weighted by all constituent elements, and low atomic number elements tended to have larger FNRCS values. The Phy-X [39,[58][59][60][61][62][63][64][65] theoretical procedure confirmed that ZnO-Bi 2 O 3 had good X-ray shielding properties within 20-200 keV, which also indicated that PAN/CFP/ZnO-Bi 2 O 3 nanofibrous membrane could attenuate X-rays within 20-200 keV.…”
Section: X-rays Shieldingmentioning
confidence: 96%
“…c) Comparison of various properties of different nanofibrous membranes. [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] fluorescent particles (CFP, Figure S1, Supporting Information) has a remarkable shielding effect on UV light, but it has large particle size and insolubility in various polar solvents, such as acetone, chloroform, and tetrahydrofuran, which greatly limits its practical application. [16,18,19] Therefore, we proposed and designed by incorporating some inorganic nanoparticles (e.g., ZnO, Bi 2 O 3 ) to plug the protection gap caused by the CFP to build a protective composite with a dense and porous structure.…”
Section: Introductionmentioning
confidence: 99%
“…The red-color dye, Rhodamine B, was successfully seen to be absorbed by the treated fiber, which contains transition metal oxides and activated carbon deposits. Similarly, Zhuojun Duan et al [13], Wafa K. Essa et al [14], and Samina Ghafoor et al [15] have shown the application of nanofibers in elimination of toxic chemicals, in environmental remediation, NF based face masks, and water remediation, respectively.…”
Section: Introductionmentioning
confidence: 95%